2000
DOI: 10.1074/jbc.275.22.16658
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cdk2-Cyclin E Complexes in Plasma Membrane and Endosomes of Liver Parenchyma

Abstract: Rat liver parenchyma Golgi/endosomes fractions harbor a tyrosine-phosphorylated 34-kDa protein. Screening of Golgi, endosomes (ENs), plasmalemma (PM), and cytosolic (Cyt) fractions revealed the presence of the mitotic kinase Cdk2 in ENs, PM, and Cyt. The fluid phase endocytic marker horseradish peroxidase gained access to the endosomal Cdk2, confirming its localization. Cdk2 was shown to be associated to cyclin E and was active in ENs and PM fractions. The administration of a single dose of insulin (1.5 g/100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 74 publications
0
30
0
Order By: Relevance
“…The protein encoded by ACK1 is localized to clathrin-containing vesicles [21], and the TXK protein binds lipid rafts via a palmitoylated cysteine-string motif [22]. Other examples included cyclin B3, whose family member cyclin B1 interacts with the cytoplasmic domain of the TM receptor PTCH [23], and cyclin E2, which has been shown to associate with endosomes and the plasma membrane of hepatocytes [24]. Thus, some genes, previously reported to be CN proteins and whose mRNAs were enriched in the membrane fraction, encode proteins that function in the cytosol, but in close association with membranes.…”
Section: Resultsmentioning
confidence: 99%
“…The protein encoded by ACK1 is localized to clathrin-containing vesicles [21], and the TXK protein binds lipid rafts via a palmitoylated cysteine-string motif [22]. Other examples included cyclin B3, whose family member cyclin B1 interacts with the cytoplasmic domain of the TM receptor PTCH [23], and cyclin E2, which has been shown to associate with endosomes and the plasma membrane of hepatocytes [24]. Thus, some genes, previously reported to be CN proteins and whose mRNAs were enriched in the membrane fraction, encode proteins that function in the cytosol, but in close association with membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Since cdk2 activity affects Stat3 phosphorylation, it most likely acts at a proximal point in the transduction pathway. In rat hepatocytes, Cdk2 has been reported to modulate receptor activation at the plasma membrane by regulating endocytosis (Gaulin et al, 2000). We have shown that the cdk2-inhibitor p27 also may interact with signaling complexes by localizing to lipid rafts (Yaroslavskiy et al, 2001) Such localization could facilitate 'inside-out' signaling of cell cycle regulators to alter signal transduction at the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…34 Accumulation of cyclinE-CDK2 complexes in s-phase of the cell cycle can be further regulated by MAPK activation. 35 In our studies we identified that PDGF temporally increases global expression of Cx43, Cx43-P, cyclin E and CDK2 proteins over a 24 hour period, and that Cx43 and cyclin E protein expression increased transiently in membrane fractions with marked reductions found between 12–24 hours.…”
Section: Discussionmentioning
confidence: 99%